ANATOMICAL AND FUNCTIONAL OUTCOME FOLLOWING PRIMARY RETINAL RE-ATTACHMENT SURGERY IN PHAKIC AND PSEUDOPHAKIC RHEGMATOGENESIS RETINAL DETACHMENT - Asghar, Asfandyar; Rehman, Aziz ur; Jafri, Waseem H; Zaman, Yawar; Bhatti, Nasir; Hassan, Mazhar ul (Journal of Ayub Medical College Abbottabad, 2010)
Background: Rhegmatogenous Retinal detachment (RRD) is relatively unusual in general population; annual incidence is 1:10,000. Objective of this study was to compare the anatomical and functional outcome of primary retinal re-attachment surgery in phakic and pseudophakic eyes. Methods: A case series comparative study was carried out at Al-Ibrahim Eye Hospital, Karachi from July 2008 to June 2009. A total of 71 eyes of 69 patients either phakic (group-I) or pseudophakic (group-II) rhegmatogenous retinal detachment (RRD) with proliferative vitreoretinopathy (PVR) up to grade C-3 were included in the study. Eyes with RRD with PVR C-4 and above, corneal opacity and previous posterior segment surgery were excluded. Pars plana vitrectomy (PPV) or scleral buckling procedure (SBP) was performed as a primary re-attachment surgery. Patients were followed for at least 6 months. Anatomical (retinal reattachment) and functional outcome (best corrected visual acuity) was noted at each follow up. Results: Anatomical outcome (retinal reattachment) was similar in group-I (93.02%) and group-II (92.86%) eyes (p=0.88). Best corrected visual acuity (functional outcome) of 6/6-6/18 was achieved in 46.5% in Group-I and 10.7% in Group-II. Raised intraocular pressure (IOP) was observed as most common complication. Conclusion: Primary retinal re-attachment surgery either in phakic (group-I) or pseudophakic (group-II) eyes have similar anatomical outcome but functional outcome depends upon the status of macula at the time of surgery and level of proliferative vitreoretinopathy (PVR). Keywords: Pars plana vitrectomy, Scleral buckling procedure, proliferative vitreoretinopathy